Eight days on planet Earth - Jordan, Cat (HarperTeen, an imprint of HarperCollinsPublishers, 2017)
"On the hot summer day Matty Jones's dad leaves for good, a strange girl suddenly appears in the empty field next to the farm... the very field in rural Pennsylvania where a spaceship supposedly landed fifty years ago. She is uniquely beautiful, sweet, and smart, and she tells Matty she's waiting for her spaceship to pick her up and return her to her home planet. Matty has heard a million impossible UFO stories: conspiracy theories, wild rumors, crazy belief in life beyond the stars. Priya must be crazy... right?" ...